HISTOLOGICAL CHANGES IN THE DUODENAL WALL IN EXPERIMENTAL PANCREATITIS - Volkov, К.S.; Shuturma, О.Ya.; Nebesna, Z.М.; Getmaniuk, І.B.; Tupol, L.D. (World of Medicine and Biology, 2018)
The morphological state of the duodenum in simulated cryogenic pancreatitis has been studied during the experiment on white rats. It has been established that on day 2 of the experiment the reactive changes occurred in the in the duodenal wall that were characterized by the dilatation of lumens and plethora of the vessels, edema of the connective tissue of the mucous and submucous membranes, thickening and deformation of the villi. On day 7 of the experiment histological changes in structural components of the duodenum became more drastic, manifested by the damage and desquamation of the columnar epithelial cells with border, edema of the stroma, leukocytic infiltration, plethora and destruction of the walls of the vessels of microvasculature, hypertrophy of the acini of the duodenal glands. On day 14 of the experiment, the lesions in duodenum wall were less pronounced in contrast to the previous time period. The plethora of the vessels, edema of connective tissue, leukocytic infiltration and damage of the cells of epithelial lamina was decreasing. The detected histological changes in the duodenum in the experimental pancreatitis are crucial in the search for effective corrective factors that will lead to normalization of its structural components.
Keywords: histological changes; duodenum; experimental pancreatitis